Endoscopic vacuum therapy for treatment of large distal anastomotic dehiscence after colorectal surgery - Mansilla-Vivar, Rodrigo (2024)
Background: Management of anastomotic dehiscences following colorectal surgery is a topic of debate. In this context, endoluminal vacuum therapy offers promising results. Objective: To analyze the efficacy and feasibility of endoluminal vacuum therapy in distal anastomotic dehiscences after colorectal surgery. Materials and methods: This study is a descriptive case series that evaluates patients with anastomotic dehiscences over a period of 18 months. All patients were treated with Endo-sponge™ (Braun Medical, Hessen, Germany). Results: Fourteen patients were included in the final analysis. The indications for endoluminal vacuum therapy were Hartmann's stump insufficency (n=6), anastomotic leakage after laparoscopic total mesorectal excision (n=4), and anastomotic dehiscence after transanal total mesorectal excision (n=4). A total of 204 sponges were placed per patient (median 12.5, range 1-33). Complete resolution was achieved in 9 patients (57.1%) in a mean time of 108 days (range 15-160 days). In the sub-analysis, patients with acute dehiscence (<3 months) achieved complete resolution in 80% (8/10), whereas no patient with chronic defects reached resolution (0/4). A low complication rate (7%) was recorded. Conclusion: Endoluminal vacuum therapy appears to be a feasible and safe treatment with a high success rate in patients with large acute colorectal anastomotic defects.